F37. Motor unit number estimation methods for quantification of motor unit loss in Guillain Barre Syndrome. (May 2018) - Nielsen, Christina S.; Vaeggemose, Michael; Jacobsen, Anna B.; Fuglsang-Frederiksen, Anders; Andersen, Henning; Harboe, Thomas; Tankisi, Hatice
Abstract : Introduction: In Guillain Barre Syndrome (GBS), axonal loss is an established predictor of poor prognosis, therefore understanding the degree of axonal loss is essential. The aim of this study was to examine the degree of axonal loss in patients with GBS using three different motor unit number estimation (MUNE) methods: MScanFit MUNE (MScan), Multipoint stimulation MUNE (MPS) and Motor Unit Number Index (MUNIX). Methods: Twenty-two GBS patients (mean age: 49.7 ± 4.3) and 24 healthy subjects (mean age: 59.5 ± 2.9) (p > 0.05) were prospectively included. MScan using Qtrac program and MPS and MUNIX using Keypoint.NET were performed in week-1 and week-4 of symptom onset on abductor pollicis brevis (APB) muscle. Additional data included, a motor Nerve Conduction Study (NCS) sum score on upper (median and ulnar) and lower extremity (peroneal and tibial) nerves, a Medical Research Council (MRC) sum score for muscle strength of 12 muscles, and EMG of the APB muscle in week-1 and week-4. Results: Mean MUNE values for MScan, MPS and MUNIX were lower in week-1 (73.4 ± 8.9, 103.5 ± 12.7 and 134.2 ± 15.7, respectively) and week-4 (68.3 ± 9.0, 105.9 ± 14.6 and 117.2 ± 15.2, respectively) for patients compared to healthy subjects (123.2 ± 6.5, 193.5 ± 15.1 and 243 ± 18.3, respectively) (p < 0.001). In week-1, MScan MUNE values correlated significantly to the MRC-sum score (r = 0.46, p = 0.029) while MPS MUNE and MUNIX values did not. In week-4 both MScan and MPS MUNE values correlated to MRC-sum score (r = 0.57 and r = 0.46, respectively, p < 0.05). MRC-sum score was not correlated to NCS-sum score in week-1 but there was a significant correlation in week-4 (r = 0.76, p < 0.001). There was no significant difference from week-1 to week-4 in the number of motor units for any of the MUNE methods or NCS-sum score (paired t-test, p > 0.05) whereas MRC-sum score increased significantly (paired t test, p < 0.05). Electromyography of APB showed denervation activity in week-1 in one patient and in week-4 in two while MUP analysis was normal in week-1 and week-4 in all patients. Conclusion: Decreased MUNE values associated with no sign of denervation already in week-1 in GBS patients suggest axonal dysfunction rather than motor unit loss. NCS did not correlate to clinical findings in week-1, however, a correlation was found to MScan. These findings may propose MScan as a sensitive electrophysiological tool to show disease severity and follow-up of GBS.